The Library as organization [soundrecording] a view from the middle - Lutz, Raymund P.; American Library Association. Conference (92nd). (Los Angeles, Calif. CREDR Corp., 1974)
A review of the basic organizational theory as it may apply to library management. It also presents a "state of the art" summary on library personnel administration and problems of promoting ideas to others. Ella Yates in this tape urges librarians to include lower level personnel in decision-making, planning, and executive directives.
Tape 1 (1 hr.). Organizational theory and patterns of management / Raymund P. Lutz -- Tape 2 (1 hr. 10 min.). The Role of middle management in personnel administration / Anthony Greco -- Tape 3 (1 hr. 10 min.). Question and answer session -- Tape 4 (1 hr. 10 min.). How to sell your ideas down the organization / Ella G. Yates -- Tape 5 (1 hr. 10 min.) Vignette: Management patterns in action -- Evaluation exercise
American Library Association 92nd annual conference. Audio cassette library for professional librarians.
Keywords: Organizational effectiveness -- Congresses; Library administration -- Congresses; Library personnel management -- Congresses; Library science; Management